Early Childhood Education in Times of Pandemic: The lived experience of children in Latinamerican countries - Marlene Fermín-González; Carolina Caffarena-Barcenilla; Blanca Barco; Ada Echenique-Arguinzones (Revista Colombiana de Educación)
In recent years, the pandemic has altered everyday relationships and social experiences. This research is framed within this context, emphasizing the concept of childhood as a social construct, historically and geographically redefined. The daily experiences and relationships of children worldwide have been significantly affected by the Pandemic. It is essential to understand these transformations through the voices of children. The primary aim of this research was to interpret the educational experiences of young children in Latin America during the Covid-19 health emergency. Data was collected through four strategies based on the mosaic approach: face-to-face interviews, virtual interviews, audio recordings, and drawings, involving a total of 46 children from 7 countries: Chile, Venezuela, Ecuador, Peru, Costa Rica, Brazil, and Argentina. The results show that during the pandemic, there were limitations on play, communication was primarily directed by teachers in virtual settings, children expressed a need for contact with peers, family mediation was crucial for learning, movement was restricted, and here was a greater emphasis on content of the didactic processes. This study aims to contribute to the positioning of participatory research with children as a necessary paradigm for addressing issues that concern them.